Financial Disagreements and Marital Conflict Tactics - Jeffrey Dew; John Dakin (Journal of Financial Therapy, 2011)
Recent studies have suggested that relative to other types of marital disagreement, financial disagreements are more problematic for couples. Using data from the National Survey of Families and Households (N = 3,861 couples), we tested whether different types of marital disagreements predicted self-reported marital conflict tactics. Considering the findings overall, financial disagreements were among the consistent top predictors of conflict tactics, including using heated arguments more frequently than calm discussion. Contrary to previous studies, however, disagreements over housework also predicted conflict tactics about as strongly as financial disagreements. Husbands’ reports of financial disagreements were more closely associated with conflict tactics than wives’ reports.
Keywords: Financial Therapy; Financial Planning; Financial Counseling